Sleep-wake differences in heart rate variability during a 105-day simulated mission to Mars - Vigo, Daniel Eduardo (2012)
Fil: Vigo, Daniel Eduardo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Departamento de Docencia e Investigación; Argentina